Creating and supporting SME opportunities in the pork value chain in Uganda - CGIAR Research Program on Livestock (2017)
The Livestock CRP generated evidence on gaps and opportunities in the pork value chain through assessments leading to intervention tests, at both farm and market levels. The work, started under Livestock & Fish, also established multi-stakeholder platforms, providing business and networking opportunities and agribusiness linkages to emerging SMEs run by farmers and young entrepreneurs. This capacity development has expanded their horizons and provided business opportunities in training, selling feeds, providing pig AI services and trading in pork.